Global, regional and national burden of decubitus ulcers in 204 countries and territories from 1990 to 2021: a systematic analysis based on the global burden of disease study 2021 - Zhang, Shenyue; Wei, Guoxing; Han, Liu; Zhong, Weibing; Lu, Zhentan; Niu, Zehao (Frontiers in Public Health, 2025)
BackgroundDecubitus ulcers, also known as pressure ulcers, pose a significant public health challenge due to their substantial impact on morbidity, mortality, and healthcare expenditures.MethodsThe number and age-standardized rates (ASRs) of prevalence, death, disability adjusted life-year (DALY), years of life lost (YLL), and years lived with disability (YLD) at the global, regional, and national levels were acquired from the GBD 2021 database. Trends were evaluated based on the estimated average percentage change (EAPC) of ASRs. Additionally, data were stratified by socio-demographic index (SDI) quantiles, regions, countries, territories, and age groups.ResultsThe total number of decubitus ulcer cases increased from 300,442 in 1990 to 645,588 in 2021. The global ASR of prevalence decreased slightly from 8.25 to 7.92 per 100,000 persons, with most cases occurring in individuals aged 60 and older. Deaths due to decubitus ulcers rose from 16,622 in 1990 to 37,033 in 2021, while the global ASR of death declined from 0.53 to 0.46 per 100,000 persons. DALY due to decubitus ulcers increased, exhibiting significant variation across regions and age groups. A higher SDI was correlated with increased ASRs of prevalence (R = 0.488, p < 0.001) and YLD (R = 0.495, p < 0.001). Conversely, a higher SDI was correlated with lower ASRs of death (R = −0.329, p < 0.001), DALY (R = −0.398, p < 0.001), and YLL (R = −0.445, p < 0.001).ConclusionThe global burden of decubitus ulcers has risen, with notable regional and age-related disparities. This study offers valuable insights for policymakers to optimize healthcare strategies and mitigate the public health impact of decubitus ulcers.